Economic stimulus policies: Analyzing the impact of "eating, traveling," and the "co-payment scheme" on the social lives of Thailand's middle and lower classes. - Sutpanpot, Pracha (Thai Social Science Journal, 2026)
This article examines the social impacts of Thailand’s economic stimulus policies implemented during and after the COVID-19 crisis, with particular attention to the Kon La Khrueng (Half-Half) scheme and consumption-based “eat and travel” programs. Rather than viewing these measures solely as economic instruments, the study conceptualizes them as policies that penetrate everyday life and shape social relations, life security, and structural inequality between the middle and lower classes in Thai society. Drawing on public policy and targeted welfare theories, class and inequality perspectives, and the political economy of consumption, the article provides a comparative analysis of policy outcomes across social classes. The findings indicate that consumption-led stimulus policies generated substantial benefits for the middle class, including the restoration of lifestyle practices, enhanced psychological security, and the preservation of social status. In contrast, the lower class experienced limited benefits due to income insecurity, precarious employment, and policy access conditions that relied heavily on digital technology and co-payment requirements. The study argues that although these policies were framed as inclusive and universal, their implementation resulted in unequal benefit distribution and contributed to the reproduction of existing structural inequalities. The article concludes that future economic policy design should move beyond consumption-oriented stimulus toward a framework that prioritizes life security, social protection, and human dignity, while explicitly acknowledging class-based differences and social contexts. Such a shift is essential for achieving more equitable and sustainable economic recovery in Thailand.